UNBRANCHED3 regulates branching by modulating cytokinin biosynthesis and signaling in maize and rice. Issue 2 (1st January 2017) - Du, Yanfang; Liu, Lei; Li, Manfei; Fang, Shuang; Shen, Xiaomeng; Chu, Jinfang; Zhang, Zuxin
Summary: UNBRANCHED3 ( UB3 ), a member of the SQUAMOSA promoter binding protein‐like ( SPL ) gene family, regulates kernel row number by negatively modulating the size of the inflorescence meristem in maize. However, the regulatory pathway by which UB3 mediates branching remains unknown. We introduced the UB3 into rice and maize to reveal its effects in the two crop plants, respectively. Furthermore, we performed transcriptome sequencing and protein‐DNA binding assay to elucidate the regulatory pathway of UB3 . We found that UB3 could bind and regulate the promoters of LONELY GUY1 ( LOG1 ) and Type‐A response regulators ( ARRs ), which participate in cytokinin biosynthesis and signaling. Overexpression of exogenous UB3 in rice ( Oryza sativa ) dramatically suppressed tillering and panicle branching as a result of a greater decrease in the amount of active cytokinin. By contrast, moderate expression of UB3 suppressed tillering slightly, but promoted panicle branching by cooperating with SPL genes, resulting in a higher grain number per panicle in rice. In maize ( Zea mays ) ub3 mutant with an increased kernel row number, UB3 showed a low expression but cytokinin biosynthesis‐related genes were up‐regulated and degradation‐related genes were down‐regulated. These results suggest that UB3 regulates vegetative and reproductive branching by modulating cytokinin biosynthesis and signaling in maize and rice.